Empirical support of the positive impact of an Intranet on communication in the working environment - Awie Leonard (Communicare)
Organizations of all shapes and sizes have to embrace information technology to survive and thrive in an increasingly competitive environment. Consequently, the level of penetration and sophistication of information technology is growing rapidly, and with it a concomitant increase in the level of organizational impact. In this article the authors investigate the impact of an Intranet on organizational issues, such as communication. The research study shows that technology like an Intranet, if used correctly, can have a very positive impact on an organization’s communication culture and as such on various other important organizational issues. The research was conducted in an insurance company in South Africa (“The Insurance Company”).